1981
DOI: 10.1007/bf01851621
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acetylcholine, gastrin, and glucagon alone and in combination with secretin and cholecystokinin on the secretion of the isolated perfused rat pancreas

Abstract: Dose-response curves of acetylcholine (ACh), gastrin, and glucagon given alone or in combination with a submaximal dose of secretin (S;' 5.0 U/h) plus cholecystokinin (CCK; 1.0 U/h) were studied in the isolated perfused rat pancreas. ACh (25 x 10-9 mol/h) increased the basal secretory flow ( mean +/- SEM: 1.19 +/- 0.22 microliter/min) by 693% and protein output (2.7 +/- 0.2 microgram/min) by 1726%. The protein secretion evoked by S plus CCK was further increased by ACh to a maximum of 26% whereas the volume se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Changes which occur in the pancreas and in its exocrine activity are probably due to the effect of fibre contained in the diet on releasing the hormones of alimentary tract (HASIK & BARTNIKOWSKA 1987), such as: CCK, secretin, gastrin, VIP and glucagon. These hormones together with acetylcholine and noradrenaline act as intermediaries in the mechanisms activating pancreatic secretion (KONTUREK 1976;SOMMER & KASPER 1981). The relationship between the presence of fibre in the diet and releasing CCK is confirmed by research carried out in humans (MÖSSNER et al 1992;BOURDON et al 2001).…”
Section: Resultsmentioning
confidence: 97%
“…Changes which occur in the pancreas and in its exocrine activity are probably due to the effect of fibre contained in the diet on releasing the hormones of alimentary tract (HASIK & BARTNIKOWSKA 1987), such as: CCK, secretin, gastrin, VIP and glucagon. These hormones together with acetylcholine and noradrenaline act as intermediaries in the mechanisms activating pancreatic secretion (KONTUREK 1976;SOMMER & KASPER 1981). The relationship between the presence of fibre in the diet and releasing CCK is confirmed by research carried out in humans (MÖSSNER et al 1992;BOURDON et al 2001).…”
Section: Resultsmentioning
confidence: 97%
“…We found that doses of ACh in the range 1-10 LM were required to produce a maximal increase in fluid secretion from isolated ducts, whereas a half-maximal response was obtained with about 0/4#M ACh. In the vascularly perfused rat pancreas it has been reported that concentrations of ACh between 041 and 3-5 /M are required to stimulate fluid secretion maximally, and that a half-maximal response is obtained with 0 05-0 09 /M ACh (Petersen & Ueda, 1977;Habara, 1980;Sommer & Kasper, 1981). These data suggest that the isolated ducts are rather less sensitive to ACh than the intact gland.…”
Section: Discussionmentioning
confidence: 90%
“…In a study in the perfused dog pancreas glucagon had no effect (72), but in a study in perfused rat pancreas, glucagon increased the basal flow and protein output. However, when glucagon was combined with secretin, it decreased the volume and protein output (91). Other in vitro studies have been carried out using pancreatic segments or lobules.…”
Section: Glucagon and The Exocrine Pancreasmentioning
confidence: 99%